Quercetin-induced miR-200b-3p regulates the mode of self-renewing divisions in pancreatic cancer. Issue 1 (December 2017) - Nwaeburu, Clifford; Abukiwan, Alia; Zhao, Zhefu; Herr, Ingrid
Abstract Background Cancer stem cells are suggested to contribute to the extremely poor prognosis of pancreatic ductal adenocarcinoma and dysregulation of symmetric and asymmetric stem cell division may be involved. Anticancer benefits of phytochemicals like the polyphenol quercetin, present in many fruits, nuts and vegetables, could be expedited by microRNAs, which orchestrate cell-fate decisions and tissue homeostasis. The mechanisms regulating the division mode of cancer stem cells in relation to phytochemical-induced microRNAs are poorly understood. Methods Patient-derived pancreas tissue and 3 established pancreatic cancer cell lines were examined by immunofluorescence and time-lapse microscopy, microRNA microarray analysis, bioinformatics and computational analysis, qRT-PCR, Western blot analysis, self-renewal and differentiation assays. Results We show that symmetric and asymmetric division occurred in patient tissues and in vitro, whereas symmetric divisions were more extensive. By microarray analysis, bioinformatics prediction and qRT-PCR, we identified and validated quercetin-induced microRNAs involved in Notch signaling/cell-fate determination. Further computational analysis distinguished miR-200b-3p as strong candidate for cell-fate determinant. Mechanistically, miR-200b-3p switched symmetric to asymmetric cell division by reversing the Notch/Numb ratio, inhibition of the self-renewal and activation of the potential to differentiate to adipocytes, osteocytes and chondrocytes. Low miR-200b-3p levels fostered Notch signaling and promoted daughter cells to become symmetric while high miR-200b-3p levels lessened Notch signaling and promoted daughter cells to become asymmetric. Conclusions Our findings provide a better understanding of the cross talk between phytochemicals, microRNAs and Notch signaling in the regulation of self-renewing cancer stem cell divisions.